2021
DOI: 10.3389/fimmu.2021.723689
|View full text |Cite
|
Sign up to set email alerts
|

Binding of Staphylococcal Enterotoxin B (SEB) to B7 Receptors Triggers TCR- and CD28-Mediated Inflammatory Signals in the Absence of MHC Class II Molecules

Abstract: The inflammatory activity of staphylococcal enterotoxin B (SEB) relies on its capacity to trigger polyclonal T-cell activation by binding both T-cell receptor (TCR) and costimulatory receptor CD28 on T cells and MHC class II and B7 molecules on antigen presenting cells (APC). Previous studies highlighted that SEB may bind TCR and CD28 molecules independently of MHC class II, yet the relative contribution of these interactions to the pro-inflammatory function of SEB remained unclear. Here, we show that binding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 85 publications
3
20
0
Order By: Relevance
“…Recent computational simulations generated on the basis of the cryoelectron microscopy of the SARS-CoV-2 spike [ 60 ] and the X-ray structure of human TCR TRAV27/TRBV19 in a ternary complex with HLA-DR1 and the staphyloccoccal SAg, SEH [ 61 ], suggested a unique putative binding site for the TCR Vβ chain near the S1/S2 cleavage site of the SARS-CoV-2 spike [ 19 ]. Further examination of the TCR Vβ-binding region on the SARS-CoV-2 spike (T 678 NSPRRARSVASQ 690 ) also suggested strong structural similarities to the superantigenic fragment of staphylococcal SEB that has been recently identified to bind to CD28 costimulatory molecules, thus triggering an inflammatory cytokine storm [ 34 , 37 , 38 , 62 ]. However, the functional relevance of this putative SAg activity of the SARS-CoV-2 spike is presently unknown [ 63 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Recent computational simulations generated on the basis of the cryoelectron microscopy of the SARS-CoV-2 spike [ 60 ] and the X-ray structure of human TCR TRAV27/TRBV19 in a ternary complex with HLA-DR1 and the staphyloccoccal SAg, SEH [ 61 ], suggested a unique putative binding site for the TCR Vβ chain near the S1/S2 cleavage site of the SARS-CoV-2 spike [ 19 ]. Further examination of the TCR Vβ-binding region on the SARS-CoV-2 spike (T 678 NSPRRARSVASQ 690 ) also suggested strong structural similarities to the superantigenic fragment of staphylococcal SEB that has been recently identified to bind to CD28 costimulatory molecules, thus triggering an inflammatory cytokine storm [ 34 , 37 , 38 , 62 ]. However, the functional relevance of this putative SAg activity of the SARS-CoV-2 spike is presently unknown [ 63 ].…”
Section: Resultsmentioning
confidence: 99%
“…After verifying the purity of the SARS-CoV-2 spike and SEB by SDS-PAGE ( Supplementary Figure S1 ), we firstly analysed the SAg activity of the SARS-CoV-2 spike on a CD28 + CH7C17 Jurkat T cell line expressing TCRVβ3.1 [ 47 , 48 ] that specifically interacts with SEB [ 67 ] and potentially with the putative CD28-binding site of the SARS-CoV-2 spike [ 19 ]. Although we have recently demonstrated that MHC-II molecules are dispensable for SEB inflammatory activity [ 38 ], the models and simulations of the SAg activity of the SARS-CoV-2 Spike have been conducted on a trimolecular complex involving HLA-DR1 [ 19 , 61 ]. Accordingly, we used murine 5-3.1/B7 cells co-expressing human HLA-DRB1*0101 and B7.1/CD80 molecules as APCs, which efficiently bind to SAgs and activate Jurkat and primary T cells without processing and presenting the derived peptides in association to MHC-II [ 38 , 47 , 68 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The area containing this motif has a strong affinity for the V-domains of both the αand β-chains of the TCR, and it shares structural similarities with Staphylococcal enterotoxin B (SEB), one of the most potent SAg [292,293]. SEB binds not only MHC-II and TCR proteins, but also contact interaction receptors CD28 (on T cells) and B7 (on APC), which play a key role in the activation of these cells, including the generation of proinflammatory cytokines [294].…”
Section: Possible Causes Of the Autoimmune And Anti-inflammatory Proc...mentioning
confidence: 99%